2016
DOI: 10.1063/1.4971228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three different methods of adding O2 additive on O concentration of atmospheric pressure plasma jets (APPJs)

Abstract: In order to maximize the O concentration generated by the atmospheric pressure plasma jets (APPJs), several different methods of adding O2 additive to working gas have been proposed. However, it is not clear, which method is capable of generating the highest concentration of O atom. In this paper, the concentration of O atoms in an APPJs by adding O2 to (1) the working gas, to (2) the downstream inside the tube, and (3) to the shielding gas is investigated by two-photon absorption laser-induced fluorescence sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…However, as mentioned above, the density of the ground states does not necessarily correlate to the density of the excited species. Interestingly, Yue et al found that the O concentration can increase even more significantly if O 2 is premixed with the working gas instead of mixed into the shielding gas. The long‐distance ROS are likely due to O 3 , which can be created through O reacting with O 2 .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…However, as mentioned above, the density of the ground states does not necessarily correlate to the density of the excited species. Interestingly, Yue et al found that the O concentration can increase even more significantly if O 2 is premixed with the working gas instead of mixed into the shielding gas. The long‐distance ROS are likely due to O 3 , which can be created through O reacting with O 2 .…”
Section: Resultssupporting
confidence: 75%
“…The reactive species produced by plasma jets are very sensitive to the environmental gas composition and any evaporation from a liquid target surface . For this reason, there have been a few studies in recent years that use a shielding gas to shroud the plasma jet and help stabilize and control plasma propagation as well as reactive species production . However, so far there is a general lack of data related to helium plasma jets with shielding gas in contact with conductive/nonconductive liquid, such as the spatial distributions of the generated reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…Ghimire et al [62,63] discussed the variation of RONS with the gap distance, electrode separation, and plasma propagation length. Yue et al [64] and Lamichhane et al [31] studied the effects of working gas on the concentration of RONS. Similarly, Lim et al [65] and Nguyen et al [66] presented the effects of the applied voltage, frequency, and moisture on atmospheric pressure plasma.…”
Section: Reactive Species Formed In Ntapp Dischargementioning
confidence: 99%
“…Plasma electron can disassociate O 2 into atomic O. This mechanism are the main conditions for the occurrence of tree reaction bodies in the formation of O 3 via Equation ( 10) [64]. In this reaction, M represents other molecules inside the reactor, such as N 2 , O 2 , Ar, He, and Ni.…”
Section: Reactive Species Formed In Ntapp Dischargementioning
confidence: 99%
“…There are several ways to generate active oxygen species in this air-methane plasma system. [41][42][43][44] The principle pathway of O production is the O 2 dissociation by electron collisions according to Equation 2.…”
Section: Diagnosis Of Optical Emission Spectralmentioning
confidence: 99%